The greenhouse gas balance of the oil palm industry in colombia: a preliminary analysis. i. carbon sequestration and carbon offsets (2012)
Colombia is currently the world’s fifth largest producer of palm oil and the largest producer in South and Central America. It has substantial areas of land that could be used for additional oil palm production and there is considerable scope for increasing yields of existing planted areas. Much of the vegetation on land suitable for conversion to oil palm has a low biomass, and so establishing oil palm plantations on such land should lead to an increase in carbon stock, thereby counteracting greenhouse gas (GHG) emissions responsible for global warming. The first part of this study examines changes in carbon stock in Colombia resulting from expansion of oil palm cultivation together with factors (offsets) that act to minimize carbon emissions. The results are subsequently used to construct a net GHG balance.